Predicting Physical Education Achievement: The Role of Sports Extracurricular Activity, Motivation, Discipline, and Responsibility - Isman Dwi Febriansyah; Soetrisno Soetrisno; Baris Yelegen; Carla Mariela Salazar-Ayala (Multidisciplinary Journal of Tourism, Hospitality, Sport and Physical Education, 2026)
Purpose of the study: This study examines the individual and joint relationships between sports extracurricular activity, learning motivation, discipline, and responsibility, and physical education achievement among eleventh-grade Science Track students at State Senior High School 1, Grobogan, Central Java, Indonesia. Methodology: A quantitative correlational cross-sectional design was employed with 84 eleventh-grade Science Track students selected via proportionate random sampling from a population of 112. Data were collected using four validated five-point Likert-scale questionnaires and official semester report card grades. Prerequisite assumption tests and multiple linear regression analysis were conducted using IBM SPSS Statistics Version 21.0. Main Findings: All four variables showed significant positive relationships with physical education achievement. Discipline demonstrated the strongest individual correlation (r = 0.833), followed by responsibility (r = 0.796), extracurricular activeness (r = 0.789), and learning motivation (r = 0.677). Simultaneous regression analysis confirmed that the four variables collectively explained 90.6% of achievement variance (R² = 0.906, F(4,79) = 190.987, p < 0.001), with responsibility yielding the highest effective contribution (27.6%). Novelty/Originality of this study: This study is the first to simultaneously examine sports extracurricular activeness, learning motivation, discipline, and responsibility as combined predictors of physical education achievement among Indonesian senior high school students within a single regression model, identifying responsibility as the dominant behavioral determinant and demonstrating the collective predictive power of affective and extracurricular variables.